Бүтэн навчит хонлэн (lagotis integrifolia schischk)- гоос ялгасан диосметиний бүтцийн судалгаа - Эрдэнэчимэг Ч; Пүрэвсүрэн С; Чимэдрагчаа Ч; Ганпүрэв Б; Батсүрэн Д (Proceedings of the Mongolian Academy of Sciences, 2017)
Lagotis integrifolia (Willd.) Schischk is an ingredient of the many traditional prescriptions and used for the treatment of fever, blood disorder, vitals disorder, diphtheria, anthrax, and pneumonia in Mongolian traditional medicine. A compound was isolated by column chromatography and HPLC methods. Molecular structures of them were elucidated by MS, 1H, 13С, HSQC, HMBC and 1Н-1Н COSY NMR method. We purified and identified as 7-dihydroxy-2-(3-hydroxy-4-methoxyphenyl) chromen-4-one (diosmetin) from the aerial parts of Lagotis integrifolia (Willd.) Schischk. Diosmetin has been obtained from this species for the first time